The use of commercial fibrin glue in dermal replacement material reduces angiogenic and lymphangiogenic gene and protein expression in vitro. (May 2023) - Fuchs, Benedikt; Birt, Alexandra; Moellhoff, Nicholas; Kuhlmann, Constanze; Giunta, Riccardo; Wiggenhauser, Paul Severin
Background: Commercial fibrin glue is increasingly finding its way into clinical practice in surgeries to seal anastomosis, and initiate hemostasis or tissue repair. Human biological glue is also being discussed as a possible cell carrier. To date, there are only a few studies addressing the effects of fibrin glue on the cell-molecular level. This study examines the effects of fibrin glue on angiogenesis and lymphangiogenesis, as well as adipose-derived stem cells (ASCs) with a focus on gene and protein expression in scaffolds regularly used for tissue engineering approaches. Methods: Collagen-based dermal regeneration matrices (DRM) were seeded with human umbilical vein endothelial cells (HUVEC), human dermal lymphatic endothelial cells (LECs), or adipose-derived stem cells (ASC) and fixed with or without fibrin glue according to the experimental group. Cultures were maintained for 1 and 7 days. Finally, angiogenic and lymphangiogenic gene and protein expression were measured with special regard to subtypes of vascular endothelial growth factor (VEGF) and corresponding receptors using Multiplex-qPCR and ELISA assays. In addition, the hypoxia-induced factor 1-alpha (HIF1a) mediated intracellular signaling pathways were included in assessments to analyze a hypoxic encapsulating effect of fibrin polymers. Results: All cell types reacted to fibrin glue application with an alteration of gene and protein expression. In particular, vascular endothelial growth factor A (VEGFA), vascular endothelial growth factor B (VEGFB), vascular endothelial growth factor C (VEGFC), vascular endothelial growth receptor 1 (VEGFR1/FLT1), vascular endothelial growth receptor 2 (VEGFR2/KDR), vascular endothelial growth receptor 3 (VEGFR3/FLT4) and Prospero Homeobox 1 (PROX1) were depressed significantly depending on fibrin glue. Especially short-term fibrin effect led to a continuous downregulation of respective gene and protein expression in HUVECs, LECs, and ASCs. Conclusion: Our findings demonstrate the impact of fibrin glue application in dermal regeneration with special regard to angiogenesis and lymphangiogenesis. In particular, a short fibrin treatment of 24 hours led to a decrease in gene and protein levels of LECS, HUVECs, and ASCs. In contrast, the long-term application showed less effect on gene and protein expressions. Therefore, this work demonstrated the negative effects of fibrin-treated cells in tissue engineering approaches and could affect wound healing during dermal regeneration.